Bandgap engineering of graphene by physisorbed adsorbates - Kozlov, Sergey M.; Vines Solana, Francesc; Görling, Andreas (Advanced Materials, 2011)
Adsorption of PTCDI induces a bandgap opening on graphene, due to the specific electronic structure of PTCDI, characterized by a LUMO energetically located in the vicinity of the Dirac point. The approach is highly versatile for bandgap engineering, tuning the bandgap by modifying the adsorption geometry, the active adsorbate coverage, or by chemical modifications of the adsorbate. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.